2011
DOI: 10.1007/s00520-011-1162-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blinded, placebo-controlled trial of ondansetron plus dexamethasone with or without metoclopramide as antiemetic prophylaxis in patients receiving high-dose cisplatin in medical practice

Abstract: The addition of metoclopramide to ondansetron plus dexamethasone reduced the use of rescue medication, but did not affect complete response rate, quality of life or adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Selective 5-hydroxytryptamine type 3 (5-HT 3 ) receptor antagonists, including ondansetron (OND) (Figure 1(b)), granisetron (GRA) (Figure 1(c)), tropisetron (TRO) (Figure 1(d)), and azasetron (AZA) (Figure 1(e)), are effective and potent antiemetic drugs which are recommended by clinical practice guidelines for patients undergoing surgery and cancer chemotherapy [36]. Literature survey has revealed that coadministration of antiemetics from different classes could be a more effective antiemetic treatment modality, and DEX is a standard component of antiemetic combination regimens with 5-HT 3 antagonists [3, 710]. Hence, mixtures of 5-HT 3 receptor antagonists, alone or in combination with DEX, are often used in clinical practice to relieve chemotherapy induced nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…Selective 5-hydroxytryptamine type 3 (5-HT 3 ) receptor antagonists, including ondansetron (OND) (Figure 1(b)), granisetron (GRA) (Figure 1(c)), tropisetron (TRO) (Figure 1(d)), and azasetron (AZA) (Figure 1(e)), are effective and potent antiemetic drugs which are recommended by clinical practice guidelines for patients undergoing surgery and cancer chemotherapy [36]. Literature survey has revealed that coadministration of antiemetics from different classes could be a more effective antiemetic treatment modality, and DEX is a standard component of antiemetic combination regimens with 5-HT 3 antagonists [3, 710]. Hence, mixtures of 5-HT 3 receptor antagonists, alone or in combination with DEX, are often used in clinical practice to relieve chemotherapy induced nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the number of patients treated with protocol 1 who experienced delayed vomiting was higher compared with those receiving protocol 12. The sample size that was used for this assessment was small; nevertheless, the evidence presented in a study by Ithimakin et al 23 supports the notion that adding metoclopramide to ondansetron and dexamethasone does not significantly improve complete response rate, the proportion of patients who develop CINV, or the severity of CINV. This may be explained by the relatively low antiemetic potency of metoclopramide.…”
Section: Discussionmentioning
confidence: 91%
“…According to a systematic review and meta-analysis by Sert NP et al, the effect of ondansetron protection on CINV cisplatin of 5-10 mg/kgBW in experimental animals ranged from 70%, if ondansetron was given 30 minutes before chemotherapy with a repeat dose 2x daily. Ithimakin's clinical study found that the complete response (CR) ondansetron-dexamethasone antiemetic combination was 50% in cisplatin chemotherapy, 6 whereas Maemondo et al said the complete protection of the palonosetron-dexamethasone antiemetic therapy combination was 81.8%. 7 The results of statistical analysis on all levels of nausea and vomiting response according to Gralla classification in this study showed significant advantages of palonosetron-dexamethasone combinations.…”
Section: Resultsmentioning
confidence: 99%
“…5 The combination of palonosetron-dexamethasone prevents nausea and vomiting after cisplatin chemotherapy 81.8%, versus 50% when given with ondansetron-dexamethasone. 6,7 In the Division of Gynecology Oncology, Dr. Soetomo Hospital, Surabaya, prophylaxis after chemotherapy (CINV) provided for HEC and MEC is a combination of ondansetron-dexamethasone.…”
Section: Introductionmentioning
confidence: 99%